Climate-Smart Bundled Small Ruminant Innovations in the Curriculum of Ethiopian Universities - Belay, Berhanu; Getachew, Tesfaye; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Relevance and quality of education are ensured by updating the curriculum with contemporary data and experiences. Universities and staff teaching courses must update the curriculum to make our curriculum need-based and meet the current changes and experiences. Including local data in our teaching and learning documents is an equally important issue. Including local data arouses students' interest and motivation to learn and ensure the relevance of education. A researcher may have data and articles from the research endeavors, and using the same data for teaching and learning eases the understanding of the chapter or the topic in the face of the students. The experience shall also help the teacher make the topic more relevant because the data is generated from the researcher's experience. The case studies could also be picked from the local research outputs, which could ultimately make part of the teaching resources to ensure the relevance of the teaching and learning efforts. This basic principle has driven us to include CBBP in Ethiopian universities' undergraduate programs. We integrated CBBP into 27 undergraduate programs in 27 Universities. The CBBP in a post-graduate program differs from the undergraduate program in terms of depth, case studies coverage, and sophistication of data analyses. The experience in the undergraduate program gave us the impetus to include CBBP in post-graduate programs. We integrated CBBP in 15 Universities and 32 post-graduate programs (26 MSc and 6 Ph.D. programs). The Universities also run CBBPs in the nearby communities, which could generate data and create a learning hub to improve the competence of graduates.